BotGo : growing pains - Mendonca, Valerie; Sharma, Supriya; Sud, Mukesh (London : Indian Institute of Management, Ahmedabad, 2019)
In 2007, Ravi Panchal, a hands-on technology buff, quit his regular 9 to 5 job to pursue his interest in robotics. He founded BotGo Technologies, an Indian robotics manufacturing company, at a time when the robotics industry in the country was still in its early stages. He designed one of India's first underwater tank cleaning robots and then progressed to more sophisticated technology with the objective of offering robotic solutions for various industries such as defence, medical equipment, space research, industrial manufacturing, and food packaging.
Originally Published InMendonca, V., Sharma, S., & Sud, M. (2019). BotGo: Growing Pains. IIMA/CIIE0014. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Robot industry -- India -- Case studies